Analysis of Topeng Jaya Perbangsa's Performance in Cirebon Regency - Restu Lanjari; Lisa Andriana (Universitas Negeri Semarang, 2023)
Jaya Perbangsa mask dance performance is a creation taken from the Mahabhrata story, with a blend of two dances between jaipong and mask dance with contemporary touch, with new types of accompaniment in West Java. The researcher's aim is to analyze the performance form of Jaya Perbangsa mask dance. This research uses a qualitative method, with an ethnochoreology approach. Data collection techniques using observation, interviews and documentation. Analysis of the performance form of Jaya Perbangsa mask dance consists of, performance structure and performance elements of Jaya Perbangsa mask dance. The dancers do not have a mandatory number, and are performed by female dancers who are required to bring a dashing Gatotkaca character, strong power, and a wide volume of motion. The makeup used by dancers uses corrective makeup with the characteristic three-braid hair.